Effect of Scandium Insertion Into the Gate-Stack of Ferroelectric Field-Effect Transistors - Kim, Bong Ho; Kuk, Song-Hyeon; Kim, Seong Kwang; Kim, Joon Pyo; Suh, Yoon-Je; Jeong, Jaeyong; Geum, Dae-Myeong; Baek, Seung-Hyub; Kim, Sang Hyeon (Institute of Electrical and Electronics Engineers, 2023)
demonstrated improved switching volt-age and retention and endurance characteristics in HfZrOx (HZO)-based ferroelectric field-effect transistors (FeFETs) via oxygen scavenging with Sc. Insertion of Sc into the gate-stack successfully reduced the thickness of the inter-facial SiOx layer (IL) between HZO and Si; thus, the FeFET with Sc could perform an immediate read-after-write at a 2-V pulse. In addition, although the IL thickness became thinner, the endurance characteristics of FeFETs with Sc were improved up to 10(10) cycles, due to the lower Vg required for the same memory window (MW) and less trapping when positive pulses are applied. We believe that this work contributes to the low-voltage operation of FeFET and proposes the potential of oxygen scavenging.